2017
DOI: 10.1002/ece3.3557
|View full text |Cite
|
Sign up to set email alerts
|

Parasite spillover: indirect effects of invasive Burmese pythons

Abstract: Identification of the origin of parasites of nonindigenous species (NIS) can be complex. NIS may introduce parasites from their native range and acquire parasites from within their invaded range. Determination of whether parasites are non‐native or native can be complicated when parasite genera occur within both the NIS’ native range and its introduced range. We explored potential for spillover and spillback of lung parasites infecting Burmese pythons (Python bivittatus) in their invasive range (Florida). We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 68 publications
1
50
0
1
Order By: Relevance
“…Primer sequences were trimmed and compared to known sequences using the NCBI Basic Local Alignment Search Tool ( 5 ). The amplified 18S sequence was 100% identical to numerous R. orientalis isolates, including those previously identified in Florida and reported by Miller et al ( 6 ) and Farrell et al ( 7 ).…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…Primer sequences were trimmed and compared to known sequences using the NCBI Basic Local Alignment Search Tool ( 5 ). The amplified 18S sequence was 100% identical to numerous R. orientalis isolates, including those previously identified in Florida and reported by Miller et al ( 6 ) and Farrell et al ( 7 ).…”
Section: Introductionsupporting
confidence: 69%
“…Raillietiella orientalis has been reported in several snake species in Asia and Australia, including those from the families Colubridae, Elaphidae, Viperidae, and Boidae ( 3 , 8 , 9 ). Raillietiella orientalis was first identified in the United States in 2017 in free-ranging, invasive Burmese pythons in the Florida Everglades as well as nine native snake species in six southern Florida counties ( 6 ) ( Figure 4 , purple counties). In that study, no parasites were identified during surveillance in northern Florida (including Alachua County) and southern Georgia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-native species can harbor parasites and pathogens capable of infecting native taxa within their introduced range, a process known as parasite spillover [13]. For species with indirect lifestyles, potential obstacles to parasite spillover include low host density and lack of an appropriate intermediate host [4].…”
Section: Introductionmentioning
confidence: 99%